On soft topological hypergroups - Gulay Oguz (Journal of Hyperstructures)
Hyperstructure theory, initiated by Marty, is a generalization theory of classical algebraic structures, while soft settheory is a powerful mathematical approach for modeling uncertainties and imprecision. In this study, it is aimed tointroduce the concept of soft topological hypergroups by presenting a soft approachto the concept of topological hypergroups, one of the topological algebraic hyperstructures. Also, by defining the concept of a soft topological transposition hypergroup, several special types of soft topological subhypergroups are presented, and then therelationships between these concepts are investigated. Later on,by constructing the category CSTH of soft topological hypergroups with soft topological homomorphisms, some related characterizations are established.